The outcomes of uterine artery embolisation (UAE) versus myomectomy for symptomatic uterine fibroids. - Azlinsuraya M,; Sobri M,; Shuhaila A,; Norzilawati MN, (Department of Surgery, UKM Medical Centre, 2014)
This was a retrospective study recruiting 40 women who had myomectomy and 13 patients who underwent UAE.